Barriers to adherence to cytology exam: a case study in low-income Colombian women - Paula C. Bermúdez; Marcela Arrivillaga; Kirvis Torres Poveda; Diana M. Castrillón Libreros; Lorena E. Castillo Castillo; Daniela Neira Acevedo (BMC, 2023)
Abstract Background Cervical cytology is essential for the early detection of cervical cancer. However, in Colombia, only 50% of women with subsidized health insurance were screened in 2019, compared to 100% of women with contributory insurance. This disparity highlights significant barriers that must be addressed. This study aimed to identify the factors that contribute to or hinder adherence to cervical cytology screening among low-income women with subsidized health insurance in a public primary care network in Cali, Colombia, from 2014 to 2018. Methods In a qualitative case study, the experience of women and health care and administrative personnel was recovered. Forty-seven women participated in seven focus group discussions. Five other women using the program participated in in-depth interviews. Finally, we interviewed eight people from the healthcare area and the health services administration. The qualitative data collected underwent content analysis, guided by the theoretical framework of Social Determinants of Health. Within this framework, five interconnected dimensions that influence adherence were incorporated. Results Adherence is a multifactorial phenomenon, and in relation to attendance at cervical cytology, the analysis delved into the mechanisms that affect it in a low-income context. Barriers to adherence were identified across multiple dimensions, including social and economic factors, health conditions, and patient-related factors, among both adherent and non-adherent women. Among adherent women, barriers and facilitators related to the healthcare team and system, as well as patient-related factors, were identified. Conclusions The findings of this research can be useful in developing personalized interventions and strategies to improve adherence and screening outcomes in low-income settings. It is necessary to increase the resources of health insurance entities to establish effective communication channels with women who attend the cervical cancer prevention program.